Enhancing Students’ Critical Thinking Through Problem-Based Learning With Socio-Scientific Issues: A Study On Stoichiometry In Grade X Science - Hajijah, Aida; Nasution, Mariam; Hasibuan, Nur Azizah Putri; Hilda, Lelya; Baroud, Najah Yousef (Jurnal Tadris Kimiya, 2025)
Understanding stoichiometry remains a significant challenge for many secondary school students, primarily due to traditional instructional approaches that emphasize memorization rather than analytical reasoning. To address this issue, this study examines the effectiveness of a socio-scientific issue (SSI)-based problem-based learning (PBL) model in fostering students’ critical thinking skills in stoichiometry instruction. The research employed a quasi-experimental design with a non-randomized pretest–posttest control group structure. Participants consisted of two grade X classes from SMAN 1 Sipirok, with one class assigned as the experimental group receiving SSI-based PBL instruction and the other as the control group receiving conventional teaching. Data were collected through essay tests designed around Ennis’s twelve critical thinking indicators. The results of an independent samples t-test indicated a statistically significant difference in posttest scores between the two groups (p = 0.027, p < 0.05), demonstrating that the experimental group outperformed the control group in critical thinking. These findings suggest that integrating socio-scientific issues into problem-based learning can effectively enhance students’ reasoning, engagement, and conceptual understanding in chemistry education. The study contributes to the ongoing discourse on innovative pedagogies by highlighting the pedagogical potential of SSI-based PBL for cultivating higher-order thinking skills in science classrooms.